Cultural intelligence of expatriate teachers in a multi-cultural education setting - Gohar, Yousra (AUC Knowledge Fountain, 2014)
The purpose of this research is to examine the impact of cultural intelligence on the level of job satisfaction and job performance among expatriate teachers working in both not-for-profit and for-profit international schools in Cairo. The importance of this study stems from the fact that globalization have led to tremendous increase in the number of international schools worldwide and in Egypt, thus allowing international schools to provide a greater share of educational services in Egypt, affecting the type and quality of education available to the public. Accordingly, it is essential to ensure that such schools are capable of providing quality education through having satisfied and highly performing expat staff. Given the limited research on the relationship between cultural intelligence and employee outcomes in the Egyptian educational sector, the study adopted the Cultural Intelligence Scale, the Teaching Satisfaction Scale, the Egyptian Labor Market Panel Survey, and the Self-Rating Survey to quantitatively measure the level of cultural intelligence, teaching satisfaction, job satisfaction, and teaching performance respectively. Four international schools in Cairo took part in this study based on convenience and judgment sampling, where 84 expatriate teachers completed the questionnaire. The results show that there is a significant positive and direct relationship between cultural intelligence and job performance, and that there is a significant positive but indirect relationship between cultural intelligence and job satisfaction among expatriate teachers. Accordingly, school principals are advised to adopt the necessary measures for ensuring that culturally intelligent expat teachers are hired, trained, and developed to be more culturally intelligent. Also, it is vital that the government take the necessary measures to ensure that international schools are taking the required steps for ensuring the presence of culturally intelligent teachers in the schools for the provision of quality education. Also the government must ensure that qualified expats are encouraged to migrate to and work in Egypt, thus allowing international schools to have a pool of qualified expat candidates to choose from.